Efficient cooling of hot spots in injection molding. A biomimetic cooling channel versus a heat‐conductive mold material and a heat conductive plastics - Berger, Gerald R.; Zorn, David; Friesenbichler, Walter; Bevc, Franz; Bodor, Christian J. (Polymer engineering and science, 2019)
This study aimed at optimizing the injection molding process of an automotive oil filter housing made from PA6.6. Mass accumulations in its design intensely increased the cooling time. In a first successful approach, a copper alloy mold insert (λ = 106 Wm−1 K−1) that contains two externally cooled heat‐conducting copper pins (λ = 310 Wm−1 K−1) was installed. We hypothesized that a biomimetic cooling channel structure in a steel mold insert would even perform superior. Using simulation software Sigmasoft® v5.0, the mold insert materials (steel Bohler X20Cr13, Ampcoloy® 83), the plastics grade PA66‐GF35 (λ = 0.27 Wm−1 K−1 or λ = 0.40 Wm−1 K−1), and three cooling designs were evaluated for their impact on cooling the hot spots in the part: the copper pin‐system, a conformal cooling channel, and blood‐vessel like channels. In the latter, the major artery branches into two sub‐arteries, which further divide into two capillary tubes each. The capillaries merge into two sub‐veins and those fuse in the major vein again. As expected, the plastics heat conductivity dominates the cooling. The biomimetic (blood‐vessel) channels, as hypothesized, cooled the major hot spot more efficient than the conformal channel and the copper pin system do. In detail, compared to the heat‐conductive insert, the cycle time may be reduced by 10 s, in spite of the lower heat conductivity λ (23.5 Wm−1 K−1) of the steel insert. Using the biomimetic (blood‐vessel) structure in a heat‐conductive mold insert would reduce the cycle time by a further second. However, raising the heat conductivity of the plastics would save another 15s. Experimental tests proved the cooling efficiency. Nevertheless, cooling channels only perform well, if they are close enough to the mass accumulation. In conclusion, transferring biologic cooling structures to injection molding seems to be promising. Ongoing advances in Additive Manufacturing will help to efficiently implement these structures into mold inserts for injection molding. POLYM. ENG. SCI., 59:E180–E188, 2019. © 2018 The Authors. Polymer Engineering & Science published by Wiley Periodicals, Inc. on behalf of Society of Plastics Engineers.